Perceived usefulness of medical teachers towards online learning using technology acceptance model - Irfan Qayyum Malik; Iqbal, Usama; Muhammad Moin; Saima Chaudhry (Journal of the Pakistan Medical Association, 2024)
Objectives: To determine medical teachers’ acceptance of and attitude towards online learning, and to gather their recommendations about how it can be incorporated in the educational system. Method: The mixed method study was conducted at Gujranwala Medical College, Gujranwala, Pakistan, from August 2021 to January 2022, and comprised medical teachers involved in online teaching during the coronavirus disease-2019 pandemic. Quantitative data was gathered using an online questionnaire based on the technology acceptance model. The qualitative component was explored through 2 focussed group discussions. Data was analysed using SPSS 25. Results: Of the 50 teachers, 31(62%) were males and 19(38%) were females. The overall mean age was 42.9±7.9 years, and the mean teaching experience was 10.9±7.9 years. Mean perceived usefulness score was 3.2±0.9 and the mean perceived ease of use score was 3.6±0.6. The mean scores were 3.3±0.9 for intention to use and 3.5±0.7 for attitude towards computer use. There was a strong positive correlation of perceived usefulness with intention to use and attitude towards computer use (p<0.05), while perceived ease of use and intention to use had a strong correlation with attitude towards computer use (p<0.05). There were total 12 participants in focussed group discussions; 2(16.7%) females and 10(83.3%) males with mean age 44.34±5.23 years. A total of 4 major themes were identified. Conclusion: Majority of medical teachers strongly agreed with the acceptance of e-learning, and agreed with its perceived usefulness and perceived ease of use for online learning. Key Words: Distance, Education, Learning, Faculty, Teachers, COVID-19.